2020
DOI: 10.1002/anie.202009663
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Symmetry Mismatch in Vaccine Nanoassembly through Spontaneous Amidation

Abstract: Matching of symmetry at interfaces is afundamental obstacle in molecular assembly.Virus-like particles (VLPs) are important vaccine platforms against pathogenic threats,i ncluding Covid-19. However,s ymmetry mismatchc an prohibit vaccine nanoassembly.W ee stablished an approach for coupling VLPs to diverse antigen symmetries.S pyCatcher003 enabled efficient VLP conjugation and extreme thermal resilience.M any people had pre-existing antibodies to Spy-Tag:SpyCatcher but less to the 003 variants.W ec oupled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 45 publications
1
65
0
Order By: Relevance
“…Although promising for protection against SARS-CoV-2, coronavirus reservoirs in bats suggest future cross-species transmission ( 6, 7, 35 ), necessitating a vaccine that protects against emerging coronaviruses as well as SARS-CoV-2. Here we prepared SpyCatcher003-mi3 nanoparticles ( 31 , 36 ) simultaneously displaying SpyTagged RBDs from human and animal coronaviruses to evaluate whether mosaic particles can elicit cross-reactive antibody responses, as previously demonstrated for influenza head domain mosaic particles ( 37 ). We show that mice immunized with homotypic or mosaic nanoparticles produced broad binding and neutralizing responses, in contrast to plasma antibodies elicited in humans by SARS-CoV-2 infection.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Although promising for protection against SARS-CoV-2, coronavirus reservoirs in bats suggest future cross-species transmission ( 6, 7, 35 ), necessitating a vaccine that protects against emerging coronaviruses as well as SARS-CoV-2. Here we prepared SpyCatcher003-mi3 nanoparticles ( 31 , 36 ) simultaneously displaying SpyTagged RBDs from human and animal coronaviruses to evaluate whether mosaic particles can elicit cross-reactive antibody responses, as previously demonstrated for influenza head domain mosaic particles ( 37 ). We show that mice immunized with homotypic or mosaic nanoparticles produced broad binding and neutralizing responses, in contrast to plasma antibodies elicited in humans by SARS-CoV-2 infection.…”
Section: Main Textmentioning
confidence: 99%
“…SpyTag003-RBDs were coupled to SpyCatcher003-mi3 (60 potential conjugation sites) ( 36 , 43 ) to make homotypic and mosaic nanoparticles (Fig 2A). Particles were purified by size exclusion chromatography (SEC) and analyzed by SDS-PAGE, revealing monodisperse SEC profiles and nearly 100% conjugation (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…To improve immunogenicity, we conjugated the RBD onto a VLP. VLP display of protein antigen has been shown to further enhance immunogenicity by facilitating antigen drainage to lymph nodes, enhancing uptake by antigen-presenting cells and increasing B cell receptor crosslinking 10,18 . Moreover, we recently showed that influenza antigens (haemagglutinin (HA) or neuraminidase (NA)) displayed on VLPs (the same VLP used in this study) were highly immunogenic at a low dose (0.1 µg) in mice 18 .…”
mentioning
confidence: 99%
“…In the present study, we used the SpyTag/SpyCatcher technology for the assembly of SARS-CoV-2 RBD on a protein nanoparticle platform, SpyCatcher003-mi3 18 . The VLP platform, based on an engineered aldolase from thermophilic bacteria, spontaneously assembles into a hollow 36-nanometre dodecahedral cage with 60 subunits 19,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation